Efficacy and safety of neoadjuvant immunotherapy in patients with microsatellite instability-high gastrointestinal malignancies: A case series. Issue 10 (October 2020) - Zhang, Zhening; Cheng, Siyuan; Gong, Jifang; Lu, Ming; Zhou, Jun; Zhang, Xiaotian; Li, Jian; Shen, Lin; Peng, Zhi
Abstract: Introduction: Immune checkpoint inhibitors (ICIs) have been approved for the late-line treatment of unresectable gastrointestinal tumors, but their efficacy and safety in the neoadjuvant setting have not been described. Whether dMMR/MSI-H populations benefit from preoperative ICIs plus surgery remains undefined. Materials and methods: Six consecutive patients managed at our institution received neoadjuvant ICIs and surgery for advanced, resectable, and MSI-H gastrointestinal tumors. All patients underwent thorough clinical evaluations and radiographic investigations before and during treatment. Next-generation sequencing (NGS), immunohistochemical (IHC) staining, and in situ hybridization (ISH) were also performed for each patient' s biopsy section to generate their molecular profiling. Results: Neoadjuvant immunotherapy was efficient and well-tolerated in patients with dMMR/MSI-H gastrointestinal tumors. Pathologic responses were observed in 6/6 (100%) dMMR/MSI-H tumors, with 5/6 (83%) complete responses. The other patient was also confirmed to demonstrate a TNM downstaging after treated with ICIs. Three patients (50%) developed grade I/II adverse events. All enrolled patients underwent timely operations without the occurrence of unexpected perioperative or postoperative complications. No disease recurrence was identified during the follow-up so far. Conclusions: Neoadjuvant immunotherapy results in favorable pathologic responses and minor adverse effects among patients with MSI-H gastrointestinal tumors. This pre-operative measure does not compromise subsequent surgery. There is an urgent need to warrant large-cohort clinical trials to examine the utility of neoadjuvant ICIs in resectable, dMMR/MSI-H gastrointestinal malignancies.